Synthesis and Biological Activity of Some 3-Aryl-3,4-dihydro-2H-benz[e]-1,3-oxazines/6-bromo-3-aryl-3,4-dihydro-2H-benz[e]-1,3-oxazines - Kumar Shukla, Davender; Rani, Manju; Ali Khan, Arif; Tiwari, Kavita; K. Gupta, Rajinder (Asian Journal of Chemistry, 2013)
N-(2-Hydroxy)-benzyl-arylamine (1) gives substantially pure 3-aryl-3,4-dihydro-2H-benz[e]-1,3-oxazines/6-bromo-3-aryl-3,4-dihydro-2H-benz[e]-1,3-oxazines (2) on cyclization with formaldehyde in methanol within 0.5-1.0 h at 65-68 ºC in excellent yields. The compounds thus prepared were screened for their antimicrobial studies against Gram-positive bacteria (Staphylococcus aureus, MTCC 96) and Gram-negative bacteria (E. coli, MTCC 739). For estimating antifungal activity the organism used is Candida albicans. Minimum inhibitory concentration of all the compounds was determined using the micro-broth dilution method.